A cross-cultural study of self-harm comparing the UK and Thailand - Anupansupsai, Rungarun (2019)
Self-harm is a serious public health concern with a large academic literature. Though different cultures have reported different self-harm prevalence, there is limited literature focusing on cultural influences on self-harm. To broaden our understanding, this thesis investigated the differences in self-harm comparing the United Kingdom and Thailand. Thailand is a growing economy, in which self-harm is increasing, but has a culture of mindfulness which has been found to manage mental health problems in other societies.